In-situ tensile tests under SEM and X-ray computed micro-tomography aimed at studying a self-healing matrix composite submitted to different thermomechanical cycles. Issue 10 (August 2017) - Bertrand, Rémi; Caty, Olivier; Mazars, Vincent; Denneulin, Sébastien; Weisbecker, Patrick; Pailhes, Jérôme; Camus, Gerald; Rebillat, Francis
Abstract: Ceramic matrix composite (CMC) based on SiC fibres and matrix is gradually introduced in aeronautical application, mostly in hottest parts of engines. Three dimensional (3D) structured materials are good candidates for complex parts such as turbine blades. Material is submitted to mechanical stresses at high temperatures in oxidizing and corrosive environments for long durations. During thermomechanical cycles, damage, oxidation and healing-phenomenon occur and develop in the material. X-ray computed micro-tomography (μCT) and tensile test under scanning electron microscopy (SEM) are experimental means to study these phenomenons. These techniques are implemented for the understanding of the behaviour of the oxide (solid or liquid) in the crack of the material. The influence of the oxide in the crack was analyzed during tensile test under SEM or μCT. The observation allows to determine the influence of the oxide on the reclosure of the crack during the unloading.